Historical narratives in the pre-Islamic era in the book Rabi` Al-Abrar by Al-Zamakhsharii - Finjan, Haifa Tarsh; Najib, Suhad Khazal (Al-Adab Journal, 2023)
One of the most prominent qualities in the pre-Islamic era was generosity, and the Arabs were distinguished by honoring the guest, and they built Hashem al-Qimmah and the ideal of that benevolent quality. And this was mentioned in the narrations of al-Zamakhshari in his book Rabi` al-Abrar on the generosity of Bani Hashim and Ibn Jadaan, and the alliance of feudal, swearing in alliances, and al-Mutayyib were mentioned, which were compared with the historical narrations reported by those who preceded the era of al-Zamakhshari and those who lived through it and those who followed it, in addition to clarifying the points of agreement and difference between these narrations and the extent of their accuracy. Al-Zamakhshari in mentioning some of the narrations and his inaccuracy in mentioning some of them, and the extent of the authenticity of his narrations and the incorrectness of some of them, as well as his criticism of others.